Kyrgyz Republic Biannual Economic Update, Fall 2015 : Resilience Amid Turbulence - World Bank Group (World Bank, Washington, DC, 2015)
GDP grew at a rate of 6.8 percent, year-on-year (y/y), between January and August, boosted by frontloaded gold production and a strong performance of the agricultural sector. Gold output grew by 46 percent (y/y), while the non-gold GDP growth rate reached 4.5 percent, up 0.9 percentage points from the same period in the previous year. However, gold production is projected to decelerate markedly during the remainder of 2015, while increasingly adverse external conditions and exchange-rate developments are expected to depress domestic consumption and private investment, as well as foreign demand. As a result, the overall growth rate for 2015 is projected to slow to 2 percent. As of August the headline inflation rate had fallen to 5.8 percent (y/y) from 10.5 percent at end-2014, but the combined effect of higher public spending and exchange-rate pressures are expected to drive up prices during the final months of the year, underscoring the importance of maintaining a tight monetary stance. Looking beyond 2015, the Kyrgyz economy is projected to recover over the medium term, and public finances are expected to stabilize, but this generally positive outlook is subject to significant downside risks. In the baseline scenario, growth is projected to accelerate to 4.2 percent in 2016, driven by higher gold production and an expected acceleration in regional economic activity. Growth in the non-gold sectors should be relatively robust at around 3.7 percent, but a slower-than-anticipated recovery in Russia and Kazakhstan could threaten this projection. Moreover, slower growth in both the domestic and regional economies could complicate the process of fiscal consolidation.